Participatory Conservation in the Philippines: The Case of Luyang Mangrove Reserve in Siquijor, Central Philippines - Chassels , Marla R.; Bucol, Abner A. (Silliman Journal, 2022)
In this paper, we present the results of a case study (conducted in 2006-2007) of Luyang Mangrove Reserve, a project managed by a local fisherfolks’ association on the island of Siquijor in the central Visayas region of the Philippines. We determined the level of environmental awareness and perception of the community on the mangrove reserve. Crucial issues and shortcomings are also presented for possible improvements of participatory conservation effort in the Philippines.